Perbandingan Efek Suplementasi Tablet Tambah Darah Dengan Dan Tanpa Vitamin C Terhadap Kadar Hemoglobin Pada Ibu Hamil Dengan Usiakehamilan 16-32 Minggu Di Desa Keniten Kecamatan Mojo Kabupaten Kediri - Siti Asiyah; Dwi Estuning Rahayu; Wiranti Dwi Novita Isnaeni (Akademi Keperawatan Dharma Husada Kediri, 2014)
The needed of Iron Tablet in pregnancy was increase than mother who not pregnant. That cause of high metabolism at the pregnancy for formed of fetal organ and energy. One of effort for prevent anemia in mother pregnant with giving the Iron tablet and vitamin c. The reason of this research in 4 June – 11 July 2014 is for compare the effect of iron tablet suplementation with and without vitamin C toward Hemoglobin level in mother pregnant With Gestational Age Of 16-32 Weeks In Desa Keniten Kecamatan Mojo Kabupaten Kediri. This research method using comparative analytical. Research design type of Quasy Eksperiment that have treatment group and control group. Treatment group will giving by Iron tablet and 100 mg vitamin C, and control group just giving by iron tablet during 21 days. Population in this research are all of mother pregnant with Gestational Age Of 16-32 Weeks with Sampling technique is cluster random sampling is 29 mother pregnant. Comparison analysis of iron tablet suplementation effect with and without vitamin C toward Hemoglobin level in mother pregnant With Gestational Age Of 16-32 Weeks, data analysis using Mann Whitney U-test and the calculated U value (44,5) less than U-table (51). So there was difference of iron tablet suplementation effect with and without vitamin C toward Hemoglobin level in mother pregnant With Gestational Age Of 16-32 Weeks Therefore, the addition of vitamin C on iron intake is needed to increase the uptake of iron tablets. When the amount of iron uptake increases, the reserves of iron in the body will also increase, so as to prevent anemia in pregnant women Keywords : Iron Tablet (Fe), Vitamin C, Hemoglobin level, Mother Pregnant